2003
DOI: 10.1024//1421-0185.62.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between text structure representation and situation model in hypertext reading

Abstract: Hypertext research results suggest that building a correct representation of the hypertext structure enables users to navigate effectively within the text. Therefore, text comprehension processes involved in hypertext reading should be investigated. In an experimental study, we differentiated the text structure from the dimensions of a postulated coherent situation model in order to compare them. Three electronic text versions, varying in navigational facility, and text structure visualization were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Having an idea of how a Web site is organized is crucial (ALA, 2011; Schrock, 1999). The structure of a Web site plays an important role in helping readers navigate through the site and read information on it (Calisir & Gurel, 2003;McDonald & Stevenson, 1998;Nimwegen, Pouw, & Oostendorp, 1999;Rouet & Levonen, 1998;Waniek, Brunstein, Naumann, & Krems, 2003). Getting familiar with the organization of a Web site helps readers understand the content (Coiro & Dobler, 2007).…”
Section: Organization Of the Web Sitementioning
confidence: 99%
“…Having an idea of how a Web site is organized is crucial (ALA, 2011; Schrock, 1999). The structure of a Web site plays an important role in helping readers navigate through the site and read information on it (Calisir & Gurel, 2003;McDonald & Stevenson, 1998;Nimwegen, Pouw, & Oostendorp, 1999;Rouet & Levonen, 1998;Waniek, Brunstein, Naumann, & Krems, 2003). Getting familiar with the organization of a Web site helps readers understand the content (Coiro & Dobler, 2007).…”
Section: Organization Of the Web Sitementioning
confidence: 99%
“…Not all hypertext systems have been found to enhance learning, though. Poorly designed systems can either have no effect on learning or lead to disorientation and cognitive overload (Baylor, 2001; Calisir & Gurel, 2003; Dias, Gomes, & Correia, 1999; McDonald & Stevenson, 1996, 1998; Waniek, Brunstein, Naumann, & Krems, 2003; Zhang, Han, Zhu, & Zhu, 2002). These potential problems are partly addressed by providing good navigational aids (Chou, Lin, & Sun, 2000; Dias et al, 1999; Lee, 2002; Lee & Tedder, 2004), although research has also shown individual differences in how users react to variations in site organization.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Nevertheless, high interconnectedness led to a more efficient navigation strategy as evidenced by a smaller number of pages that had to be navigated to complete the task. One reason why an effect of interconnectedness was (Naumann et al 2001, Waniek et al 2003) did produce significant differences perhaps due to differences in the content used. Also, an overview of the hypertext structure was displayed in a frame on the left-hand side which might have guided users' orientation, an effect reported in many other studies as well (e.g.…”
Section: Users' Structural Modelmentioning
confidence: 94%